Graduate Medical Education in Otolaryngology: Making Dollars and Sense of Reform. (13th April 2021) - Chen, Jenny X.; Shah, Shivani A.; Rathi, Vinay K.; Varvares, Mark A.; Gray, Stacey T.
Abstract : Graduate medical education (GME) is funded by the Centers for Medicare and Medicaid Services through both direct and indirect payments. In recent years, stakeholders have raised concerns about the growth of spending on GME and distribution of payment among hospitals. Key stakeholders have proposed reforms to reduce GME funding such as adjustments to statutory payment formulas and absolute caps on annual payments per resident. Otolaryngology departmental leadership should understand the potential effects of proposed reforms, which could have significant implications for the short‐term financial performance and the long‐term specialty workforce. Although some hospitals and departments may elect to reduce resident salaries or eliminate positions in the face of GME funding cuts, this approach overlooks the substantial Medicare revenue contributed by resident care and high cost of alternative labor sources. Commitment to resident training is necessary to align both the margin and mission of otolaryngology departments and their sponsoring hospitals.